Community pharmacy & primary care integration: qualitative study on stakeholders' opinions and interventions - Amaia Urionagüena; Celia Piquer-Martinez; Shalom Isaac Benrimoj; Begoña Calvo; Victoria Garcia-Cardenas; Fernando Martinez-Martinez; Miguel Angel Gastelurrutia (Taylor & Francis Group, 2024)
Background Health systems worldwide are under pressure. Integration seems a possible solution to improve healthcare systems efficiency. This research aims to gather stakeholders' opinions on integrating community pharmacy and the primary healthcare system and secondly to explore and prioritise interventions for an initial integration plan.Method Using a constructivist qualitative research approach, a two-phase qualitative study was conducted in the Basque Country, Spain. Thematic analysis using NVivo® was undertaken on data gathered during focus groups and semi-structured interviews (phase 1). During phase 2, a nominal group prioritised potential integration interventions identified in phase 1.Results The study amalgamated findings from four focus groups and nine interviews, revealing six themes. Stakeholders had a diverse understanding of integration, associating the term mainly with collaboration, communication or cooperation. Community pharmacies were positively perceived; however, their commercial and privately owned nature was of concern. Remuneration methods for pharmacists were controversial, with a suggested shift to service-based remuneration. Information availability and barriers such as interprofessional communication gaps were highlighted. The nominal group prioritised, according to importance and feasibility, bidirectional communication development, coordination in using interprofessional protocols and community pharmacist participation in primary healthcare centre meetings as interventions for integrating community pharmacies and primary healthcare centres.Conclusion Based on the opinions of stakeholders, three interventions are proposed to initiate the integration process of community pharmacy and primary care. The implementation of these interventions will need to be negotiated with the relevant authorities and evaluated.